Technical and Economic Assessment of Gold and Silver Recovery from Zinc Pressure Leach Residue by a Pyrometallurgical Method - J. M. Skeaff (The Minerals, Metals and Materials Society, 1989)
As much as 100% of the gold and 67% of the silver in a sulphur-bearing hydrometallurgical leach residue have been transferred to copper metal at copper smelting temperatures by dissolving the partially calcined residue in an iron-bearing slag maintained in equilibrium with the liquid copper metal and matte phases. The precious metals can then be recovered by conventional refining techniques. Copper can be recycled at least four times without any detrimental effects on gold and silver transfers and recoveries. Apparent copper recovery in the .process can be over 100% because of the copper content of the residue. Based on slag analys.es, the overal1 recovery of gold in the copper metal and matte phases varies from 94% to 100% under all conditions investigated. On the? same basis, silver recovery varies .from 9S% ?to 99% under optimum conditions, but is only 4S% to 73% under other, less attractive conditions. Unaccounted for silver losses of' about 30% make it difficult to determine the major factors affecting ?silver transfer and recovery. A method for implementing the technology on a commercial scale at a Canadian copper/zinc smelter has been proposed. A preliminary economic assessment and comparison of the proposed pyrometallurgical process with conventional cyanidation indicates that either process is economically attractive for recovering gold and silver from leach residues. Although the capital costs are higher, the pyrometallurgical process is simpler, has higher recoveries, lower operating costs and no .potential environmental problems related to cyanide disposal.